Inactivation of Phospholipase D Diminishes Acinetobacter baumannii Pathogenesis - Jacobs, Anna C. (American Society for Microbiology (ASM), 2010)
Acinetobacter baumannii is an emerging bacterial pathogen of considerable health care concern. Nonetheless, relatively little is known about the organism's virulence factors or their regulatory networks. Septicemia and ventilator-associated pneumonia are two of the more severe forms of A. baumannii disease. To identify virulence factors that may contribute to these disease processes, genetically diverse A. baumannii clinical isolates were evaluated for the ability to proliferate in human serum. A transposon mutant library was created in a strain background that propagated well in serum and screened for members with decreased serum growth. The results revealed that disruption of A. baumannii phospholipase D (PLD) caused a reduction in the organism's ability to thrive in serum, a deficiency in epithelial cell invasion, and diminished pathogenesis in a murine model of pneumonia. Collectively, these results suggest that PLD is an A. baumannii virulence factor.